P-98 Environmental contamination with and internal occupational exposure to antineoplastic agents and evaluation of genotoxic and epigenetic effects thereof. (14th March 2023) - Verscheure, Eline; Creta, Matteo; Vanneste, Dorian; Adhithya, Srinivasan; Vanoirbeek, Jeroen; Zakia, Meziane; Abdesselam, Taleb; Lebegge, Robin; Poels, Katrien; Duca, Radu-Corneliu; Ghosh, Manosij; Godderis, Lode
Abstract : Introduction: It is important to monitor unintended exposure to antineoplastic drugs (ANDs) and potential effects occurring after exposure. Our aims were to develop a method sensitive enough to measure trace levels of ANDs in urine, evaluate environmental contamination and occupational exposure to ANDs. Finally, we aimed to study the link between exposure and genotoxic/epigenetic effects. Materials and Methods: UPLC-UniSpray-MS/MS was used for quantification of ANDs in urine (n=83), while UPLC-ESI-MS/MS was used for analysis of wipe samples (n=62) collected in 6 different departments from a university hospital. Novum simplified liquid cartridges were used for extraction of urine samples, liquid extraction was used for wipe samples. The link between exposure and effects was studied through a systematic review. Results and Conclusions: A method for urine analysis was fully developed and validated with LLOQs of 0.05 ng/mL, 0.3 ng/mL and 0.7 ng/mL for cyclophosphamide, ifosfamide and paclitaxel, respectively. All wipe samples and 17 urine samples had quantifiable concentrations of at least one compound. Concentrations in urine ranged from <LOQ-15.80ng/mL and in wipes from <LOQ- 208.85 ng/cm 2 . The highest levels were observed in the oncology department. Despite the numerous guidelines, healthcare workers are thus still exposed to ANDs, therefore, actions should be taken to limit the presence of ANDs in the work environment. In the systematic review, we confirmed the possibility of genotoxic damage after occupational exposure to ANDs. However, we revealed a lack of data on biomonitoring, epigenetic effects, exposure-effect link. Therefore, in the next phase, we will generate valuable information on the concentration-effect link. Ethical approval: 'Conseil d'Ethique et de Déontologie de l'Université de Tlemcen' (15/12/2016). Funding: Industrieel Onderzoeksfonds KU Leuven Program: C3 project: (C32/15/029) Occupational dermal exposure to cytostatics (3M170331). The Research Foundation – Flanders (1SD2322N). The authors declare no conflict of interest.